No Acute Toxicity Tests of Purwoceng (Pimpinella pruatjan Molk.) Ethanolic Extract on Male Albino Rat by Determined Hepatorenal Function Test and Histopathology - Fitranto Arjadi; Dhadhang Wahyu Kurniawan; Yudhi Wibowo; Wahyu Siswandari; Lantip Rujito (Universitas Jenderal Soedirman, 2019)
Pimpinella pruatjan Molkis a local indegineuos plant speciescommonly used aphrodisiac.This studywas performed to analyze the effect of acute administration of purwoceng (Pimpinella pruatjan Molk.) roots ethanol extract to liver and kidney histological damagein rats. The study used an experimental approachusing post test only with control group design. Rats were randomly divided into five groups; 3 rats in each group. Group A as a control group received aquadest, group B, C, D, and E were given purwoceng roots ethanol extract dose of 5 mg/kgBW, 50 mg/kgBW, 300 mg/kgBW, and 2000 mg/kgBW respectively.Liver histological damage was assessed by a modification of the Roenigk score, whereaskidney damage was by the semiquantitative scoring of proximal tubular necrosis. UV test was used to quantify the AST and ALT levels, the measurement of blood urea levels was using the Urease-GLDH method, and Jaffe methodwas used to access the creatinine levels.Kruskal-Wallis test showed that liver and kidney histologicalparameterswere not significantly affected, as well as theblood urea and creatinine levels (p>0.05).Meanwhile,ALT level wasonly parameters which showed the significant test (p <0.05)among groups. Study concluded that the liver and kidney histological appearance, AST, blood urea, and creatinine levels in the male albino rat were not significantly affected by acute administration of Purwoceng roots in various dosesbut the ALT level was significantly affected